Specialty grand challenge: emergency health services - Chan, Theodore C. (Frontiers in Disaster and Emergency Medicine, 2023)
Introduction Emergency health services encompasses a wide-ranging, diverse, and overarching impact on the health and wellbeing of individuals, communities, and large populations everywhere. The recent COVID pandemic, where emergency care providers played a leading and often heroic role in the response highlights the critical importance of emergency healthcare staff and infrastructure. , Emergency Medicine is at the intersection of acute medical care at the individual level and public health at the population level. Moreover, the specialty is relatively new within the House of Medicine, developing its specific training and areas of expertise only in the mid late 20th century. , As such, the field of Emergency health services faces both great challenges and unique opportunities as the specialty continues to grow and expand its impact.